Some pro- and anti-inflammatory cytokines, their genetic polymorphism and postinfarct cardiac remodeling - A. M. Nikolaeva; N. P. Babushkina; V. V. Ryabov (Российский кардиологический журнал)
The role of molecular genetic factors in cardiovascular disease (CVD) development has been actively studied in recent years. In patients with acute myocardial infarction and heart failure, the genetic component contributes to the determination of inflammation and persistence of inflammatory mediators in the myocardium. The genetic component in combination with traditional CVD risk factors determines the clinical course of the disease, the severity and its outcome. This review summarizes the data on relationship of proand anti-inflammatory cytokines with coronary artery disease and its clinical manifestations.